Integrated machine learning-guided developing high-performance desulfurization adsorbents based on fragmented feature strategy - Haikuo Shen; Wenyuan Tao; Qidong Zhao; Donghai Lin; Yonghou Xiao (Journal of Environmental Chemical Engineering, 2026)

Co-occurring Spirogyra sp. and enrofloxacin stressors interact to alter macrophyte interactions: evidence from a freshwater mesocosm experiment - Yuqing Tian; Cheng Lin; Xu Zhang; Hui Yang; Hongzhi Mao; Heyin Wang; Jiali Chen; Donghai Zhang; Jiangtao Hu; Xusheng Gong; Junyan Wu; Yuying Li; et al. (Aquatic Sciences, 2026)

Microbial carbon use efficiency and necromass turnover drive persistent carbon formation in paddy soils under straw-returned complex rotation - Yinhang Xia; Jun Chen; Donghai Jiang; Jiao Lin; Yan Xiao; Yongxue Yan; Tingsen Mou; Yeqin Shu; Nader Saad Elsayed; Yumei Chen; Georg Guggenberger; Zhenhua Zhang (Soil and Tillage Research, 2026)

Introducing Double-Moment Warm Rain Physics into the Goddard 4ICE Microphysics Scheme - Kao-Shen Chung; Yu-Jyun Liou; Cheng-Rong You; Zhao-Cheng Zeng; Pay-Liam Lin; Donghai Wang; Wei-Kuo Tao; Stephen Lang; Takamichi Iguchi; Adrian Loftus; Jiun-Dar Chern (Asia-Pacific Journal of Atmospheric Sciences, 2026)
In this study, a new double-moment warm rain Goddard 4ICE scheme (GCEDM) is developed based on the Goddard 4ICE single-moment (GCESM) scheme and then tested using idealized 2D squall line and 3D supercell simulations. The addition of the total number concentrations for cloud water ( $$\:N_{TC}$$ ) and rainwater ( $$\:N_{TR}$$ ) enables this new scheme to simulate more diverse raindrop size distributions, making it more realistic. GCEDM has similar overall thermal and dynamic characteristics to GCESM but produces higher evaporation rates, predicted particle number concentrations, and mass mixing ratios than GCESM, leading to stronger cold pools than with GCESM. In addition, comparisons are made versus the Weather Research and Forecasting Model Double-Moment Microphysics 7-class scheme (WDM7), which was also improved from a single-moment 4-class ice scheme to a double-moment warm-rain scheme. WDM7 also shows a stronger cold pool, but the system characteristics and microphysical processes are quite different from the single-moment version of this scheme.

Self-reporting and high-energy supercapacitors enabled by electrochromic ZnCo-S@CuFe-LDH heterostructures via interfacial engineering - Jiale Hou; Zhenghu Zhu; Haofeng Lu; Hecong Wang; Cheng Chen; Xinfeng Wu; Yonghou Xiao; Wanghui Wei; Minjie Xue; Lexing You; Xinzhou Ma; Donghai Lin (Chemical Engineering Journal, 2026)

Motion reduction performance of a novel dual-mode TLCD for floating offshore wind turbine - Donghai Li; Shenghui Huang; Lin Lin; Shilun Zhao; Chongwei Zhang (Ocean Engineering, 2025)

Chaotic climate system forecasting using an improved echo state network with sparse observations - Lin Ding; Yulong Bai; Donghai Zheng; Xiaoduo Pan; Manhong Fan; Xin Li (Science China Earth Sciences, 2025)

Zero-valent iron on graphite-cellulose biochar catalysts for the Fenton degradation of tetracycline from water - Shuai Chen; Yuanchuan Zhao; Guilan Gao; Hao Dong; Feng Yuan; Donghai Lin; Jie Guan; Aleksandra Nesic; Junli Xu; Carolina Belver; Jorge Bedia (Process Safety and Environmental Protection, 2024)

The impacts of forest resources, green investment, healthcare, and education on environmental pollution: China Carbon neutrality program - Donghai Huang; Huajie Shen; Yuan Miao; Rongfeng Ding; Yang Lin; Hongying Tan (Journal of Cleaner Production, 2024)

N-doped porous carbon material derived by MOFs calcined in proper oxygen atmosphere as high-performance catalyst for the low-temperature NH3-SCR - Jiexuan Zhu; Donghai Mo; Lin Tao; Jinfeng Li; Shiying Fu; Lihui Dong; Bin Li; Zhengjun Chen; Minguang Fan (Journal of Environmental Chemical Engineering, 2023)

Non-destructive determination of internal defects in chestnut (Castanea mollissima) during postharvest storage using X-ray computed tomography - Jiahua Wang; Zelin Lu; Xiaofeng Xiao; Mengting Xu; Yuqing Lin; Huang Dai; Xiaodan Liu; Fuwei Pi; Donghai Han (Postharvest Biology and Technology, 2023)

Synthesis of zero-valent iron supported with graphite and plastic based carbon from recycling spent lithium ion batteries and its reaction mechanism with 4-chlorophenol in water - Guilan Gao; Zhuoxiang Li; Shuai Chen; Carolina Belver; Donghai Lin; Zixiang Li; Jie Guan; Yaoguang Guo; Jorge Bedia (Journal of Environmental Management, 2023)

Sources, Aging, and Management of Coastal Plastics in Shanghai - Shuai Chen; Donghai Lin; Guilan Gao; Jie Guan; Carolina Belver; Jorge Bedia (Water, Air, & Soil Pollution, 2022)

Solution structure and backbone dynamics for S1 domain of ribosomal protein S1 from Mycobacterium tuberculosis - Biling Huang; Shihui Fan; Yan Liu; Yufen Zhao; Donghai Lin; Xinli Liao (European Biophysics Journal, 2019)

Bacillus thuringiensis targets the host intestinal epithelial junctions for successful infection of Caenorhabditis elegans - Liting Wan; Jian Lin; Hongwen Du; Yulan Zhang; Alejandra Bravo; Mario Soberón; Ming Sun; Donghai Peng (Environmental Microbiology, 2019)
Summary Pathogenic bacteria use different strategies to infect their hosts, including the simultaneous production of pore forming toxins and several virulence factors that may synergize their pathogenic effects. However, how the pathogenic bacteria are able to break out the host intestinal barrier is poorly understood. The infectious cycle of Bacillus thuringiensis (Bt) bacterium in Caenorhabditis elegans is a powerful model system to study the early stages of the infection process. Bt produces Cry pore‐forming toxins during the sporulation phase that are key virulence factors involved in its pathogenesis. In this study, we show that Bt disrupts the intestinal epithelial junctions of C. elegans at early stages of infection allowing Bt bacterium to complete its life cycle in the worm. We further confirmed that the vegetative Bt cells trigger a quorum sensing response that is activated by PlcR regulator, resulting in production of different virulence factors, such as the metalloproteinases ColB and Bmp1, that besides Cry toxins are necessary to disrupt the nematode epithelial junctions causing efficient bacterial host infection and death of the nematode. Our work provides new insights into the pathogenesis of Bt and highlights the importance of breaking down host epithelial junctions for a successful infection. A similar mechanism could be used by other pathogen‐host interactions since epithelial junctions are conserved structures from insects to mammals.

Pranlukast, a novel binding ligand of human Raf1 kinase inhibitory protein - Tao Sun; Zhihua Wu; Mengyao Luo; Donghai Lin; Chenyun Guo (Biotechnology Letters, 2016)

A novel metalloproteinase virulence factor is involved in B acillus thuringiensis pathogenesis in nematodes and insects - Donghai Peng; Jian Lin; Qiong Huang; Wen Zheng; Guoqiang Liu; Jinshui Zheng; Lei Zhu; Ming Sun (Environmental Microbiology, 2016)
Summary The Gram‐positive soil bacterium B acillus thuringiensis has been developed as the leading microbial insecticide for years. The pathogenesis of B . thuringiensis requires common extracellular factors that depend on the PlcR regulon, which regulates a large number of virulence factors; however, the precise role of many of these proteins is not known. In this study, we describe the complete lifecycle of a nematicidal B . thuringiensis strain in the free living nematode C aenorhabditis elegans using in vitro and in vivo molecular techniques to follow host and bacterial effectors during the infection process. We then focus on the metalloproteinase ColB , a collagenase, which was found highly important for destruction of the intestine thereby facilitates the adaptation and colonization of B . thuringiensis in C . elegans. In vivo green fluorescent protein ( GFP ) reporter‐gene studies showed that ColB expression is highly induced and regulated by the global activator PlcR . Finally, we demonstrated that ColB also takes part in B . thuringiensis virulence in an insect model following injection and oral infection. Indeed, addition of purified ColB accelerates the action of Cry toxin proteins in insects, too . These results give novel insights into host adaptation for B . thuringiensis and other B . cereus group bacteria and highlight the role of collagenase metalloproteases to synergize infection process.

Enhanced hydroxyl radical generation in the combined ozonation and electrolysis process using carbon nanotubes containing gas diffusion cathode - Donghai Wu; Guanghua Lu; Ran Zhang; Qiuhong Lin; Zhenhua Yan; Jianchao Liu; Yi Li (Environmental Science and Pollution Research, 2015)

Structural basis for RKIP binding with its substrate Raf1 kinase - Zhihua Wu; Cuiping Fu; Lina Shi; Lu Ruan; Donghai Lin; Chenyun Guo (Biotechnology Letters, 2014)

Spatiotemporal changes in vegetation coverage and its driving factors in the Three-River Headwaters Region during 2000–2011 - Xianfeng Liu; Jinshui Zhang; Xiufang Zhu; Yaozhong Pan; Yanxu Liu; Donghai Zhang; Zhihui Lin (Journal of Geographical Sciences, 2014)

Transgenic Amorphophallus konjac expressing synthesized acyl-homoserine lactonase (aiiA) gene exhibit enhanced resistance to soft rot disease - Huifang Ban; Xinli Chai; Yongjun Lin; Ying Zhou; Donghai Peng; Yi Zhou; Yulan Zou; Ziniu Yu; Ming Sun (Plant Cell Reports, 2009)